(untitled) (Global Journal of Human-Social Science, 2017)
Election is always controversial in Ethiopia This part of controversies also part of Toke Kutaye woreda of west shewa zone of Oromia regional state Public political participation particularly during election looks like a tragedy in the woreda because the end result always comes with a dilemma The ways through which people mobilized for political participation mainly for election by the ethnic parties of the same ethnic group to solve the claim of the people also a headache and strike full in this woreda In contrast the people of the woreda were less likely aware of the program and policy of political parties The election administrative body makes a baised decision in favor of the ruling regime The methodological approach used was both qualitative and quantitative approach to clearly identify the core problem of electoral practice in the woreda